Changes in Behaviors and Outcomes Among School-Based Employees in a Wellness Program. Issue 6 (November 2017) - LeCheminant, James; Merrill, Ray M.; Masterson, Travis D.
Objective . To examine the health behavior changes and mental-health and job-related outcomes of school-based employees over 2 years while participating in a worksite wellness program. Method . All participants in this analysis (n = 1, 873) were employees of a large public school district in the western United States and voluntarily enrolled in a comprehensive wellness program. Exercise level, fruit and vegetable consumption, restful sleep, smoking, alcohol consumption, self-rated health, mental health-related outcomes (stress, depression, life-satisfaction, and loneliness), and job-related outcomes (job performance, absenteeism, job-related satisfaction) are reported. Results . There was an increase in days and minutes/week exercised, fruit/vegetable consumption, days per week of restful sleep, and a decrease in alcohol consumption (ps < .037) over 2 years. Among those who reported smoking, the number of days smoked increased after 1 year but then dropped below baseline levels at year 2 (p < .0001). Several mental health-related outcomes improved (ps < .033); however, job performance was slightly lower (↓ 2%), and the other job-related outcomes were unchanged. Conclusion . School employees may benefit from a comprehensive worksite wellness program, particularly to improve health behaviors. However, mental health and job-related outcome results were mixed over 2 years.